Positron Emission Tomography Imaging of Pancreatic Cancer - Krishnamoorthy, Saravanan Kokila; Jambawaliker, Sachin; Saif, Muhammad Wasif (JOP. Journal of the Pancreas, 2014)
Positron emission tomography (PET) using 18F-fluorodeoxyglucose (FDG) is increasingly used for the staging of solid malignancies, including lung and esophagus. However, controversy still exists in relation to the application of PET in pancreatic cancer. The authors review seven studies (Abstracts #183, #189, #190, #254, #357, #375, #378) presented at the 2014 ASCO Gastrointestinal Cancers Symposium and discuss on the role of PET in this disease. As the limitations of the Response Evaluation Criteria In Solid Tumors (RECIST) continue to become evident, FDG-PET may identify changes in the metabolic activity within pancreatic adenocarcinoma, and can provide both diagnostic and prognostic information. Image: Multiple metastases in the liver (Figure 1c)